Critical Discourse Analysis of Increasing Subsidized Fuel Price in 2022 by President Joko Widodo - Afrilia Ernes Natasya; Suko Widodo; Santi Isnaini (Jurnal Nomosleca, 2024)
This research aims to uncover the meaning and ideology in the text of the speech as well as uncover the motives of certain interests related to President Joko Widodo's policy of increasing subsidized fuel prices. The method used is explanatory qualitative, the research object used is a transcript of the text of the speech on the increase in subsidized fuel prices on September 3 2022 by President Joko Widodo through triangulation. The results of the research show that in the text of the speech President Joko Widodo mentioned the word protect, but this diction was not in line with the data also conveyed in the text that the increase in subsidized fuel prices was caused by an increase in the APBN and inappropriate targets for subsidized fuel consumption enjoyed by the well-off. These two reasons for the increase in subsidized fuel prices actually illustrate the government's powerlessness in prioritizing the welfare of the people who should be prioritized in obtaining subsidized fuel.